Intelligent Networked Things 5th China Conference, CINT 2022, Urumqi, China, August 7-8, 2022, Revised Selected Papers - Zhang, Lin.; Yu, Wensheng; Jiang, Haijun; Laili, Yuanjun (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the 5th China Conference on Intelligent Networked Things, CINT 2022, held in Urumqi, China, during August 7-8, 2022. The 45 full papers included in this book were carefully reviewed and selected from 130 submissions. They were organized in topical sections as follows: Access, Perception, and Prediction in Intelligent Networked Things, Control of Intelligent Networked Things and Modeling, Simulation and Optimization of Intelligent Networked Things.
Access, Perception, and Prediction in Intelligent Networked Things -- Prediction of the Melt Pool Size in Single-layer Single-channel Selective Laser Melting Based on Neural Network -- Implementation of Underwater Vehicle Pipeline Inspection Based on Machine Vision -- Underwater Target Tracking Algorithm Based on Optical Flow -- Risk Monitoring Data Upload System for Safety Production of Hazardous Chemicals -- Joint Feature Fusion Approach to Human Pose Estimation Using mmWave Rader -- Question Answering Based On Entity-aware Self-attention -- TGNN:A GNN-based Method with Multi-Entity Node for Personal Banking Time Prediction -- Spatial-Temporal Adaptive Graph Convolution with Attention Network for Traffic Forecasting -- Sentiment Analysis of Online Travel Reviews Based on Capsule Network and Sentiment Lexicon -- A Sentiment Analysis Model for Car Review Texts Based On Adversarial Training and Whole Word Mask BERT -- Bi-Convolution Matrix Factorization Algorithm Based On Improved ConvMF -- A Novel Defect Detection Method for Insulators of Power Transmission Line Based on YOLOv5 -- Multi-Objective Optimization Based Viscosity Prediction for Inks in Direct Ink Writing Numerical Simulations -- A Meta-Learning-Based Object Detection Method for Custom Grasping in Human-Robot Collaboration -- A knowledge-Embedding-Based Approach for Process-Decision Knowledge Mining -- A Knowledge Content Matching Degree Calculation Method Supporting Process Knowledge Recommendation -- Control of Intelligent Networked Things -- Fault-tolerant Control for Underwater Vehicle with Actuator Saturation and Faults -- Event-Triggered Kernel Recursive Least Squares Algorithm -- Distributed Fault-Tolerant Formation Control of Nonholonomic Mobile Robots with SSA Parameter Optimization -- Set-Membership Estimation for Nonlinear Parameter-Varying Systems -- Adaptive Synchronization of Fractional-Order Multiplex Networks via Quantized Control -- Synchronization in Fixed/Preassigned time of Inertial Neural Networks with Time-varying Delay -- A Deep Reinforcement Learning Based Leader-Follower Control Policy for Swarm Systems -- Research on the Key Technology of Digital Twin-driven Fracture Reduction Robot Force Control -- A Data-driven Feedforward Control Design Method for Nonlinear Systems -- Tracking Error Boundary of Novel Stable Inversion Based Feedforward Control for a Class of Non-minimum Phase Systems -- Modeling, Simulation and Optimization of Intelligent Networked Things -- Resource Scheduling Algorithm for Heterogeneous High-Performance Clusters -- ieSTGCN:A Mining Model of Skeleton Spatio-temporal Graph -- Deep Recurrent Q-Network for Cloud Manufacturing Scheduling Problems -- Fixed-Time Bipartite Consensus for Multi-agent Systems Subjected to External Disturbances -- Study on Method of Extraction and Clustering of Model Construction Style -- Evaluation of Motion Planning Algorithms for Underground Mobile Robots -- Optimization of Ethanol Fermentation Based on Design of Dynamic Experiments -- Uncertain Economic order Quantity Model for Perishable Items with Shelf Life -- Distributed Processing of Continuous Range Queries over Moving Objects -- Scaled Consensus of Switched Multi-agent Systems with Controller Failure and Time-Varying Delay -- Resilient Event-Triggered Distributed Resource Allocation for Multi-Agent Systems under DoS Attacks -- A Method and Implementation of Automatic Requirement Tracking and Verification for Complex Products Based On X Language -- Global Mittag-Leffler Stability of Fractional-Order Inertial Complex-Valued Neural Networks -- Distributed Fixed-Time Consensus and Optimization for Second-Order Multi-Agent Systems -- Emergency Evacuation Route Planning of Cruise Ship Based on Intelligent Optimization Algorithm -- Model Library System Based on Multi-Domain Simulation Model Integration Interface -- Multi-Agent Path Finding Algorithm of Merged Node Rule and Bounded Focal Search -- Dynamic Scheduling Method of Multi-objective Job Shop Based on Reinforcement Learning -- A Runtime Verification Tool for Distributed Simulation Systems.
Keywords: Artificial intelligence; Computer Networks; Intelligence Infrastructure; Computer Networks; Artificial Intelligence